The Energy Demand Elasticity in Relation to Gross Domestic Product in Indonesia: Sectoral Approach - Suharno, Suharno; Anwar, Nurul (International Journal of Energy Economics and Policy, 2023)
This paper aims at estimating the energy demand elasticity in relation to gross domestic product in Indonesia based on data from 1995 to 2018. The sectors examined are industry, trading, transportation, and housing sectors. The method of analysis is the Autoregressive Distributed Lag (ARDL). An interesting estimation result here is that the elasticity of the industry sector is negative both short and long term. The other three sectors show positive elasticity. This paper contributes to the discussion of the energy demand ARDL model to be used as a reference in developing countries.